Rural entrepreneurial ecosystems: A systematic literature review for advancing conceptualisation - Evelyn Calispa Aguilar (Entrepreneurial Business and Economics Review (EBER), 2021)
Objective: The objective of the article is to identify the specific contextual factors and mechanisms that are important for the functioning of entrepreneurial ecosystems in rural areas. Research Design & Methods: Qualitative analysis of 70 high-quality articles which results from a systematic literature review. Findings: Rural poverty, natural resources endowment, peripheral location, and rural cultural values are important features of rurality which influences entrepreneurial ecosystems' performance in several ways. Implications & Recommendations: Features of rurality are yet to be embedded into current general entrepreneurial ecosystem frameworks as they have the potential to enhance models' capacity to capture local aspects when employed to understand and measure entrepreneurship in rural contexts. Contribution & Value Added: This study makes an important contribution by identifying the relevant factors and mechanisms associated with entrepreneurial ecosystems in rural contexts from the emerging literature in rural entrepreneurship.
Keywords: L26; 330; rural entrepreneurship; rural entrepreneurial ecosystem; entrepreneurial ecosystem